2011
DOI: 10.1021/np200051j
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and NF-κB Inhibitory Constituents of the Stems of Cratoxylum cochinchinense and Their Semisynthetic Analogues

Abstract: A new caged xanthone (1), a new prenylxanthone (2), seven known xanthones, and a known sterol glucoside were isolated from the stems of Cratoxylum cochinchinense, collected in Vietnam. Compounds 1 and 2 were determined structurally by analysis of their spectroscopic data. In addition, five new (10 and 16–19) and eight known prenylated xanthone derivatives were synthesized from the known compounds, α-mangostin (3) and cochinchinone A (6). Several of these substances were found to be cytotoxic towards HT-29 huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 43 publications
3
92
0
Order By: Relevance
“…The absolute configuration at C5 and C7 were determined as 5S and 7R via the ECD spectra which displayed a positive and a negative Cotton effect near 290 and 360 nm, respectively. Based on the NOESY and CD spectroscopic data the absolute configuration of C10a and C27 were deduced as 10aS and 27S (Ren et al, 2010(Ren et al, , 2011b. The CD spectrum of cochinchinoxanthone (114) showed negative and positive Cotton effect at 292 and 353 nm.…”
Section: Sources and Structure Diversity Of Prenylated Caged Xanthonesmentioning
confidence: 99%
“…The absolute configuration at C5 and C7 were determined as 5S and 7R via the ECD spectra which displayed a positive and a negative Cotton effect near 290 and 360 nm, respectively. Based on the NOESY and CD spectroscopic data the absolute configuration of C10a and C27 were deduced as 10aS and 27S (Ren et al, 2010(Ren et al, , 2011b. The CD spectrum of cochinchinoxanthone (114) showed negative and positive Cotton effect at 292 and 353 nm.…”
Section: Sources and Structure Diversity Of Prenylated Caged Xanthonesmentioning
confidence: 99%
“…12,35 All arylnaphthalene lignans isolated from P. poilanei in the present study and their semisynthetic analogues were evaluated for their cytotoxicity against HT-29 human colon cancer cells, using paclitaxel and etoposide as the positive controls (Table 3). 38 Compounds 1−4, 7, and 8 were found to be cytotoxic, of which 1 and 7 were the most potently active, with IC 50 values of 170 and 110 nM, respectively, but compounds 5, 6, and etoposide were inactive. Inspection of the lignan structures and their cytotoxicity showed that compounds containing more lipophilic acetyl groups exhibit higher potency, so the presence of one or more acetyl groups linked to the arabinose residue improved the resultant cytotoxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…To partially discern the effects of both the arabinose unit and the acetyl group in the mediation of cytotoxicity of the diphyllin lignans, two previously reported analogues were prepared. (7) was produced by acetylation of 1 and 4 using a standard method 38 and was identified by its molecular formula of C 32 H 30 O 14 , as determined by HRESIMS and comparison of its spectroscopic data (Supporting Information) with those reported for a synthetic sample. 32 The aglycone diphyllin (8) was generated by hydrolysis of phyllanthusmin C (4), and its structure was determined by comparison of its spectroscopic data with reference values.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTB-38) and MCF-7 was obtained from National Cancer Institute. HT-29 cytotoxicity assay was performed as previously described (Ren et al, 2011). As for MCF-7 cytotoxicity assay, cell line was grown in Roswell Park Memorial Institute (RPMI)-1640 medium with Lglutamine purchased from Mediatech Inc., supplemented with 10% fetal bovine serum purchased from Atlanta Biologicals (GA, USA) and 1% w/v Gibco 1 Antibiotic-Antimycotic solution purchased from Life Technologies, and incubated in humidified incubator with an atmosphere of 95% air and 5% CO 2 at 37 C. The cells were sub-cultured when they reached 80-90% confluence.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%